Animal Histories of the Civil War Era - Hess, Earl J. (Book collections on Project MUSE., 2022)
"Animal Histories of the Civil War Era introduces the concept of animal history to Civil War studies. Until now, the field of animal history has paid little attention to the Civil War, and Civil War scholars have paid almost no attention to animals. This volume serves as an intersection of these two critical fields of scholarly inquiry. In thirteen essays, ten by Civil War historians and three by animal history scholars, the contributors illuminate an important but largely ignored aspect of the war-its animal participants. The topics covered are wide-ranging. One essay examines camels in the American South and Southwest before the war, highlighting the involvement of camels in illegal efforts to import slaves into the United States. Essays on horses during the war explore the process of procuring equines for military service, the training of horses for use by artillery units, and the impact of horse supply problems on hopes for Confederate military success. Two essays cover wildlife in the Civil War, focusing on bees. An essay on hogs in the Confederacy and another on the culture of meat-eating examine animals as food during the war. Two essays on dogs in the South during and after the war illustrate how pets and farm animals influenced slavery and the prosecution of the Confederate war effort. An essay on regimental animal mascots during the war analyzes how veterans incorporated them into their post-war lives. Another essay explores the effort to create a national zoo in the 1880s, a task that underscored the persistence of sectional division after Reconstruction. The final essay likewise examines sectional division and the resonance of enslavement as seen in the career of an ex-slave and his unusual show horse. Through the process of broadly writing animals into Civil War history, the contributors demonstrate the many ways in which animals of all kinds played roles in the sectional history of America during the middle and late nineteenth century. Most of the essays incorporate animal history theory and concepts to bring added meaning to their topics. Even those essays that do not explicitly cross-disciplinary boundaries provide a deep understanding of how particular animals influenced the shape and contour of Civil War history. Was the deadly conflict of 1861-1865 a watershed in animal awareness and advocacy among Americans? The authors suggest that the answer may well be an emphatic yes"--